Thermal effect on the leachability of extraframework Co2+ in zeolite X. (February 2021) - Park, Minji; Kim, Sookyung; Han, Young-Soo; Hyun, Sung Pil; Jeong, Hoon Young
Abstract: A partially Co 2+ -exchanged zeolite X was thermally treated to simulate the effect of decay heat on the leachability of extraframework Co 2+ . To have a mechanistic insight into thermal effect, X-ray diffraction, scanning electron microscopy, 27 Al magic angle spinning nuclear magnetic resonance spectroscopy, and Co K-edge X-ray absorption spectroscopy were employed with leaching tests. Although thermal treatment at ≤ 600 °C did not lead to the collapse of zeolite framework, it removed H2 O molecules from the coordination shell of extraframework Co 2+, which in turn changed its coordination structure in a way to strengthen the interaction between Co 2+ and the lattice oxygens. In leaching tests, the sample treated at higher temperature for a longer period showed less remobilized Co 2+ by forming a Co(OH)2 -like surface precipitate and a Co hydrotalcite-like phase. Notably, the formation of the latter phase indicated the abstraction of the framework Al, the extent of which increased with the treatment temperature and duration. Two mechanisms, the concurrent extraction of Al with Co 2+ remobilization and the hydrolysis-promoted Al abstraction, were proposed to account for thermally promoted dealumination. This study suggests that the exposure of Co 2+ -exchanged zeolite X to decay heat lessen the risk of extraframework Co 2+ to be reintroduced into groundwater. Graphical abstract: Image 1 Highlights: By thermal treatment at ≤ 600 °C, Co 2+ -exchanged zeolite X maintains its framework. Thermally induced dehydration promotes the dealumination of zeolite X. Liberated Co 2+ via exchange can be re-immobilized by forming Co hydroxide phases. Exposure to decay heat lowers the leachability of extraframework Co 2+ in zeolite X.